Energy and protein requirements of Holstein × Gyr crossbred heifers. (6th September 2020) - Castro, M. M. D.; Albino, R. L.; Rodrigues, J. P. P.; Sguizzato, A. L. L.; Santos, M. M. F.; Rotta, P. P.; Caton, J. S.; Moraes, L. E. F. D.; Silva, F. F.; Marcondes, M. I.
Abstract : Nutrient requirements in cattle are dependent on physiological stage, breed and environmental conditions. In Holstein × Gyr crossbred dairy heifers, the lack of data remains a limiting factor for estimating energy and protein requirements. Thus, we aimed to estimate the energy and protein requirements of Holstein × Gyr crossbred heifers raised under tropical conditions. Twenty-two crossbred (½ Holstein × ½ Gyr) heifers with an average initial BW of 102.2 ± 3.4 kg and 3 to 4 months of age were used. To estimate requirements, the comparative slaughter technique was used: four animals were assigned to the reference group, slaughtered at the beginning of the experiment to estimate the initial empty BW (EBW ) and composition of the animals that remained in the experiment. The remaining animals were randomized into three treatments based on targeted rates of BW gain: high (1.0 kg/day), low (0.5 kg/day) and close to maintenance (0.1 kg/day). At the end of the experiment, all animals were slaughtered to determine EBW, empty body gain (EBG ) and body energy and protein contents. The linear regression parameters were estimated using PROC MIXED of SAS (version 9.4). Estimates of the parameters of non-linear regressions were adjusted through PROC NLIN of SAS using the Gauss–Newton method for parameter fit. The net requirements of energy for maintenance (NE m ) and metabolizable energy for maintenance (ME m ) were 0.303 and 0.469 MJ/EBW 0.75 per day, respectively. The efficiency of use of ME m was 64.5%. The estimated equation to predict the net energy requirement for gain (NE g ) was: NE g (MJ/day) = 0.299 × EBW 0.75 × EBG 0.601 . The efficiency of use of ME for gain ( k g ) was 30.7%. The requirement of metabolizable protein for maintenance was 3.52 g/EBW 0.75 per day. The equation to predict net protein requirement for gain (NP g ) was: NP g (g/day) = 243.65 × EBW −0.091 × EBG. The efficiency of use of metabolizable protein for gain ( k ) was 50.8%. We observed noteworthy differences when comparing to ME and protein requirements of Holstein × Gyr crossbred heifers with other systems. In addition, we also observed differences in estimates for NE m, NE g, NP g, k g and k . Therefore, we propose that the equations generated in the present study should be used to estimate energy and protein requirements for Holstein × Gyr crossbred dairy heifers raised in tropical conditions in the post-weaning phase up to 185 kg of BW.